THE SPREAD OF BASKETBALL AROUND THE WORLD AND THE DEVELOPMENT OF BASKETBALL IN DIFFERENT COUNTRIES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This scientific article analyzes the spread of basketball worldwide and the development process of the sport in different countries. It focuses on the historical development of basketball and the unique characteristics of modern basketball, highlighting how it has become one of the most popular and widespread sports in the 21st century. The article discusses the global popularity of basketball, the factors influencing its spread, and the achievements in the development of basketball in various countries. Additionally, it presents various strategies and approaches that have been implemented to promote the sport's growth.